Shortening the Application Time of Alcohol-Based Hand Rubs to 15 Seconds May Improve the Frequency of Hand Antisepsis Actions in a Neonatal Intensive Care Unit. (30th October 2017) - Kramer, Axel; Pittet, Didier; Klasinc, Romana; Krebs, Stefan; Koburger, Torsten; Fusch, Christoph; Assadian, Ojan
Abstract : BACKGROUND: For alcohol-based hand rubs, the currently recommended application time of 30 seconds is longer than the actual time spent in clinical practice. We investigated whether a shorter application time of 15 seconds is microbiologically safe in neonatal intensive care and may positively influence compliance with the frequency of hand antisepsis actions. METHODS: We conducted in vitro experiments to determine the antimicrobial efficacy of hand rubs within 15 seconds, followed by clinical observations to assess the effect of a shortened hand antisepsis procedure under clinical conditions in a neonatal intensive care unit (NICU). An independent observer monitored the frequency of hand antisepsis actions during shifts. RESULTS: All tested hand rubs fulfilled the requirement of equal or even significantly higher efficacy within 15 seconds when compared to a reference alcohol propan-2-ol 60% (v/v) within 30 seconds. Microbiologically, reducing the application time to 15 seconds had a similar effect when compared to 30-second hand rubbing, but it resulted in significantly increased frequency of hand antisepsis actions (7.9±4.3 per hour vs 5.8±2.9 per hour; P =.05). CONCLUSION: Time pressure and workload are recognized barriers to compliance. Therefore, reducing the recommended time for hand antisepsis actions, using tested and well-evaluated hand rub formulations, may improve hand hygiene compliance in clinical practice. Infect Control Hosp Epidemiol 2017;38:1430–1434